An Update on the Role of Adipose Tissues in Psoriasis - Wong, Yisheng; Nakamizo, Satoshi; Tan, Kahbing J.; Kabashima, Kenji (Frontiers in Immunology, 2019)
Psoriasis is a common chronic inflammatory skin disease that is increasingly being recognized as a disease that not only affects the skin but also has multi-systemic implications. The pathophysiological link between psoriasis and obesity is becoming increasingly elucidated by recent studies. The cross-talk between adipocytes and the immune system via various mediators such as adipokines could explain how obesity contributes to psoriasis. The effects of obesity on adipocytes include upregulation of pro-inflammatory adipokines such as leptin and resistin, downregulation of anti-inflammatory adipokine, and also the stimulation of pro-inflammatory cytokine production by macrophages. This article provides an update on the role of adipose tissues in psoriasis.